Aberrant generation of dentate gyrus granule cells is associated with epileptic susceptibility in p53 conditional knockout mice - Ruiz-Reig, Nuria; Chehade, Georges; Yerna, Xavier; Durá, Irene; Gailly, Philippe; Tissir, Fadel (Frontiers in Neuroscience, 2024)
Neuronal apoptosis is a mechanism used to clear the cells of oxidative stress or DNA damage and refine the final number of neurons for a functional neuronal circuit. The tumour suppressor protein p53 is a key regulator of the cell cycle and serves as a checkpoint for eliminating neurons with high DNA damage, hyperproliferative signals or cellular stress. During development, p53 is largely expressed in progenitor cells. In the adult brain, p53 expression is restricted to the neurogenic niches where it regulates cell proliferation and self-renewal. To investigate the functional consequences of p53 deletion in the cortex and hippocampus, we generated a conditional mutant mouse (p53-cKO) in which p53 is deleted from pallial progenitors and their derivatives. Surprisingly, we did not find any significant change in the number of neurons in the mutant cortex or CA region of the hippocampus compared with control mice. However, p53-cKO mice exhibit more proliferative cells in the subgranular zone of the dentate gyrus and more granule cells in the granular cell layer. Glutamatergic synapses in the CA3 region are more numerous in p53-cKO mice compared with control littermates, which correlates with overexcitability and higher epileptic susceptibility in the mutant mice.